Correlation of Pelvic Parameters with Isthmic Spondylolisthesis - Shrestha, S.; Lakhey, R. B.; Paudel, S.; Kafle, D.; Pokharel, R. (Kathmandu University Medical Journal, 2021)
Background Spondylolisthesis is one of the major causes of low back pain. The anterior shift of the vertebra is mostly at L4 and L5 levels. Several types have been described, most common being the isthmic type. Pelvic parameters are said to be associated with development and progression of listhesis, and should be evaluated while treating it. Objective To study the correlation of Pelvic parameters with isthmic spondylolisthesis. Method It was a cross sectional case control study. In 68 cases with Isthmic Spondylolisthesis and of 34 cases with low back pain without listhesis (control), the spinopelvic parameters like lumbar lordosis, pelvic incidence, pelvic tilt and sacral slopes were measured together with degree of slip with lateral radiographs. Findings were analyzed and compared with control group. Result In control group, the pelvic incidence was 50.44±4.78°, the sacral slope was 34.38±6.79°, the pelvic tilt was 15.97±5.31°, and the lumbar lordosis was 46.76±6.78°. In Isthmic Spondylolisthesis group, the pelvic incidence was 60.85±6.79°, the sacral slope was 40.40±6.91°, the pelvic tilt was 20.63±7.51°, and the lumbar lordosis was 57.31±7.11°. The difference in spinopelvic parameters amongst control and Isthmic Spondylolisthesis group was statistically significant (p < 0.001). The degree of slip was directly proportional to the pelvic incidence angle (grade I=52°, II =62° and III 72.5°). Conclusion Spino-pelvic parameters are higher in isthmic spondylolisthesis group and is significantly associated with severity of the slip.